Prevention System Towards Terrorist Attacks at Police Headquarters: Astana Anyar Police Station and Indonesian National Police Headquarters Case Studies - Apriliasari, Annisa Yudha; Priyanto, Sapto (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
A terrorist attack is an act that targets vital objects that have a high intensity of activity, such as public service places (police), public facilities (places of worship), and crowd centers (tourist attractions). One of the aims of targeting attacks in crowded locations is that they can provide massive coverage and dissemination of news to create fear in the wider community. In efforts to prevent counterterrorism in Indonesia, various counterterrorism policies implemented by the government, including the crime prevention system in potential terror attack locations, have been implemented to limit the possibility of terror attacks occurring. The aim of this study is to offer recommendations for future terrorism prevention strategies, with a particular focus on police headquarters in Indonesia and regional police offices. This paper uses a qualitative approach through several primary and secondary data collection methods. The data results are described using Lifestyle Exposure and Routine Activity Theory (L-RAT), Routine Activity Theory (RAT), and Crime Prevention Through Environmental Design (CPTED). Crime prevention with the CPTED approach can be used to reduce opportunities for terrorist attacks, decrease fear of crime, improve quality neighborly relationships, and seek a safer and more secure workplace. Counter-surveillance can use analysis from the L-RAT and RAT approaches that allow changes in routine activity patterns or lifestyles to make it difficult for potential criminals to analyze and can reduce the potential for crime acts.